«Admus and Hermione» by Jean-Baptiste Lully as the first sample of the lyrical tragedy genre - Artemieva, Vira (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2024)
The relevance of the study. It consists in considering the "Cadmus and Hermione" by JeanBaptiste Lully not only in the context of the author's artistic evolution, but also as the result of the traditions of French musical and theatrical court art. Written in 1673, it became the composer's first work in genre tragédie lyrique («tragédie en musique»). The main objective of the study to determine the socio-cultural prerequisites for the emergence of Lully's first lyrical tragedy "Cadmus and Hermione" and to identify the genres that became the basis for the creation of a model of tragédie lyrique. The methodology includes biographical (to find out the circumstances of Lully's life and activities), comparative (to reveal the continuity of the considered tragédie lyrique in relation to the system of musical and theatrical genres of the 17th century), as well as structural-functional, genre-stylistic and intonational-dramatic methods (for a comprehensive analysis of the work). Results and conclusions. It is considered Lully's "Cadmus and Hermione" as a model of the French genre of the tragédie lyrique. It is emphasized that this work arose under the influence of traditions, French musical and theatrical art. The details of the production and the reaction of King Louis XIV to the premiere of the work are highlighted, which determined the further support of the composer at the royal court. The plot of the opera, the compositional and dramaturgical organization of "Cadmus and Hermione", which served as a reference point in Lully's further work in the genre of tragédie lyrique, are analyzed. It is noted that the plot borrowed from Ovid's "Metamorphoses" is based on the travels of Cadmus (his many victories and happy love) and is a prophecy of a happy future in the conception of absolutist art. It was concluded that when creating the first sample of the genre of tragédie lyrique, the composer strongly relied on the developed genre system of French music and theater art. In particular, the connections of tragédie lyrique with court ballet, comedy-ballet, air de cour and other genres were noted. The influences of the traditions of the French dramatic theater on the construction of the plot and the peculiarities of the vocal parts of the tragédie lyrique are revealed, and the presence of features of the Italian comic opera is indicated. It is emphasized that the long-term experience of the performer, the intuition of the musician and the talent of the composer were embodied in the first example of the genre of tragédie lyrique in Lully's work. The considered work became a model of the genre of tragédie lyrique, which was fundamental for France in the 17th and 18th centuries, which, in particular, determined Lully's prominent place in the history of French music.